Cape Verde : Poverty Reduction Strategy Paper Preparation Status Report. (IMF Staff Country Reports; Country Report ;, 2003)
This paper examines the Poverty Reduction Strategy Paper (PRSP) Preparation Status Report for Cape Verde. On the road map to full PRSP, significant progress has been made in the context of preparation of the PRSP. The government has approved the National Development Plan (NDP). The programs and sub-programs incorporated in the NDP are quadrennial (2002-05). The financing gap will be reassessed in light of the review of the macroeconomic framework supported by a Poverty Reduction and Growth Facility arrangement.